2004
DOI: 10.1002/pmic.200300570
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the effect of heat stress on hexaploid wheat grain: Characterization of heat‐responsive proteins from non‐prolamins fraction

Abstract: The effect of heat stress on hexaploid wheat grain proteome was recently analyzed in our previous works. Proteomic tools allowed the characterization of heat-responsive proteins of total endosperm, composed mainly of prolamins. The present work completes this study; our aim was to analyze the effect of heat stress on the water-soluble fraction, composed essentially of albumins and globulins. These proteins were separated by two-dimensional electrophoresis (2-DE), visualized by Coomassie Brilliant Blue (CBB) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
107
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 43 publications
9
107
1
2
Order By: Relevance
“…ATP synthase, a multisubunit complex that spans the inner membrane, is the main enzyme of the ATP biosynthetic pathway. The catalytic site for ATP synthesis is localized primarily on the beta-subunit; ATP is produced from ADP in the presence of a proton gradient across the Mt membrane and a decrease in the amount of ATP synthase may affect energy-dependent processes involved in heat stress resistance [12]. Taken together, these results suggest that the energy production systems of plants are highly affected by heat stress and increases of the chloroplastidal F1 alpha subunit possibly re-establish this system.…”
Section: Energy and Metabolismsmentioning
confidence: 89%
See 1 more Smart Citation
“…ATP synthase, a multisubunit complex that spans the inner membrane, is the main enzyme of the ATP biosynthetic pathway. The catalytic site for ATP synthesis is localized primarily on the beta-subunit; ATP is produced from ADP in the presence of a proton gradient across the Mt membrane and a decrease in the amount of ATP synthase may affect energy-dependent processes involved in heat stress resistance [12]. Taken together, these results suggest that the energy production systems of plants are highly affected by heat stress and increases of the chloroplastidal F1 alpha subunit possibly re-establish this system.…”
Section: Energy and Metabolismsmentioning
confidence: 89%
“…The current status of rice proteomic analysis has been reviewed recently [10], but there still are no reports regarding the effects of heat stress on rice leaves. Thus far, there have been only a few proteomic studies regarding heat stress in plants [3,5,[11][12][13]. To the best of our knowledge, only one proteomic analysis has been carried out during the caryopsis development of rice under heat stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…When comparing results on Chlamydomonas with proteomics studies conducted on various land plants (Skylas et al, 2002;Majoul et al, 2003Majoul et al, , 2004Süle et al, 2004;Ferreira et al, 2006;Lee et al, 2007;Palmblad et al, 2008;Valcu et al, 2008;Xu and Huang, 2008;Scafaro et al, 2010;Xu and Huang, 2010), we concluded that the upregulation of chaperones, FKBP65 orthologs, and thiamine biosynthesis protein and the downregulation of ferredoxin-NADP(H) oxidoreductase, Rubisco, methionine synthase, adenosylhomocysteinase, and S-adenosylmethionine synthetase are conserved in the green lineage. However, there were also many inconsistencies between these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The albumin and globulin fractions represent about 9 and 5% of wheat seed proteins, respectively, and they are mainly present in embryo and aleurone (Singh and Skerritt 2001). The molecular weights of albumins and globulins are mostly between 12 to 60 kD, with the high molecular weight (HMW) albumins in the range of 45Á65 kD and triticins 22Á58 kD (Singh and Skerritt 2001;Bean and Tilley 2003;Majoul et al 2004). In some cases, HMW albumins and triticins are storage proteins, which have the characteristics of wheat storage proteins Shepherd 1985, 1987;Gupta et al 1991).…”
mentioning
confidence: 99%
“…Mots clé s: Triticum aestivum, ble´tendre, prote´ines hydrosolubles, e´lectrophore`se capillaire, marqueurs biochimiques Wheat grain proteins are classified into two major groups: the main storage proteins of the endosperm (gliadins and glutenins) called prolamins, and the nonprolamins consisting of water-soluble (WS) albumins and salt-soluble globulins (Majoul et al 2004). The albumin and globulin fractions represent about 9 and 5% of wheat seed proteins, respectively, and they are mainly present in embryo and aleurone (Singh and Skerritt 2001).…”
mentioning
confidence: 99%